THE BUCCAL MUCOSA IN ANAEMIA - Jacobs, Allan (1960)
The histological features of the buccal mucosa have been examined in 50 cases of iron-deficiency anaemia, 14 cases of megaloblastic anaemia, and 50 normal subjects. Differences between the anaemic and normal groups have been found and in some anaemic patients striking morphological changes have been seen. These might be due to a direct effect of iron or vitamin B(12) deficiency on the metabolism of the epithelial cells.